Evaluation capacity building—Results and reflections across two years of a multisite empowerment evaluation in an HIV prevention context. (December 2018) - Lindeman, Peter T.; Bettin, Emily; Beach, Lauren B.; Adames, Christian N.; Johnson, Amy K.; Kern, Dave; Stonehouse, Patrick; Greene, George J.; Phillips, Gregory
Highlights: Empowerment Evaluation leads to evaluation capacity building in diverse settings. Staff from 20 agencies reported significantly increased overall evaluation capacity. Engagement in evaluation planning and technical assistance led to built capacity. Evaluation capacity building did not differ across different types of organizations. Program funders, staff, and evaluators should work together to encourage engagement. Abstract: As the need for rigorous evidence of program efficacy increases, integrating evaluation activities into program implementation is becoming crucial. As a result, external evaluators are placing increased focus on evaluation capacity building as a practice. However, empirical evidence of how to foster evaluation capacity in different contexts remains limited. This study presents findings from an evaluation capacity survey conducted within a multisite Empowerment Evaluation initiative, in which an external evaluator worked with 20 project teams at diverse community agencies implementing HIV prevention projects. Survey results revealed representatives from project teams (n = 33) reported significantly higher overall evaluation capacity after engaging with the external evaluator on planning and implementing their evaluation. Improvements differed across organization type, intervention type, staff position, and reported engagement on various activities throughout the course of the evaluation. Results indicated empowerment evaluation and other stakeholder-focused evaluation approaches are broadly applicable when evaluation capacity building is a desired outcome, particularly when able to engage project staff in the planning of the evaluation and in delivering technical assistance services. Accordingly, efforts should be made by program funders, staff, and evaluators to encourage active engagement starting in the early stages of program and evaluation planning.